An overview of floating tablet - Borude, Shubham Sakharam; Mandhare, Trushali A.; Pooja S.Kashid,; Otari, Kishor (Asian Journal of Pharmaceutical Research and Development, 2024)
Flash nanoprecipitation (FNP) is a widely used technique for preparing particulate carriers based on various polymers that has been shown to be a promising technology for the industrial production of drug-loaded nanoparticles. The use of amphiphilic block copolymers as a stabilizer to protect the nanoparticles from aggregation makes flash nanoprecipitation (FNP) an ideal method for rapidly preparing nanosized drug particles with high drug-loading efficiency. Flash nanoprecipitation (FNP) is a controlled antisolvent precipitation process that has been shown to be effective for producing drug nanoparticles with a defined mean particle size and narrow particle size distribution. However, the physical instability of the generated nanoparticles remains a significant barrier to the use of this technology in pharmaceutical formulation. This review discusses the use of FNP to create poorly water-soluble drug nanoparticles using controllable mixing devices such as confined impinging jets mixers (CIJM), multi-inlet vortex mixers (MIVM), and a variety of other microfluidic mixer systems. The mechanisms and processes of drug nanoparticle formation by FNP are described in detail. Then, during the FNP process, the supersaturation level and mixing rate are controlled to tailor the ultrafine drug nanoparticles, as well as the influence of drugs, solvent, anti-solvent, and stabilizers. The control of supersaturation level and mixing rate during the FNP process to tailor ultrafine drug nanoparticles is discussed, as well as the influence of drugs, solvent, anti-solvent, stabilizers, and temperature on fabrication.